High-performance wear-resistant granite ceramic tile for public places and preparation method thereof

By adopting compound phase wear-resistant ceramic body formula and three-dimensional fabric and particle preparation technology, the problem of insufficient wear resistance and three-dimensional decoration effect of existing imitation granite ceramic tiles is solved, and the preparation of high-performance wear-resistant granite ceramic tiles is achieved, satisfying the Decoration needs in public places.

CN119409481APending Publication Date: 2025-02-11MARCOPOLO HLDG CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411486781.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing imitation granite ceramic tiles have shortcomings in wear resistance and three-dimensional decorative effects, which limit their wide application in public scenes.

Method used

The compound phase wear-resistant ceramic body formula is used, combined with three-dimensional fabrics and particle preparation technology, granite ceramic tiles with high hardness, wear resistance, pollution resistance and high radioactivity are prepared to achieve their wide application in public places.

Benefits of technology

Through this technical means, the wear resistance and three-dimensional decorative effect of granite ceramic tiles are improved, the decoration needs of public places are met, and the scope of application is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409481A_ABST
    Figure CN119409481A_ABST
Patent Text Reader

Abstract

The invention relates to a high-performance wear-resistant granite ceramic tile for public places and a preparation method thereof. The high-performance wear-resistant granite ceramic tile for the public place comprises a complex-phase wear-resistant ceramic green body, and is prepared from the following raw material components in percentage by weight: 8 to 15 percent of ball clay, 8 to 15 percent of high-whiteness kaolin, 10 to 15 percent of mixed mud, 0 to 5 percent of calcined talc, 3 to 6 percent of bentonite, 15 to 25 percent of kalialbite powder, 8 to 15 percent of finely ground lithium tailings, 4 to 8 percent of calcined bauxite and 15 to 25 percent of fine corundum powder, 0%-5% of superfine zirconium silicate, 0%-5% of high-purity anatase titanium dioxide powder, 0%-1% of a green body reinforcing agent and 1%-3% of a dispergator; according to the present invention, the complex phase blank formula is adopted, and the three-dimensional cloth and particle preparation technology is combined to prepare the blank, such that the obtained material has advantages of high hardness, good wear resistance, good pollution resistance, high strength, low radioactivity and other physical and chemical properties, and can perfectly present the three-dimensional texture effect of the granite stone material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic tiles, and in particular relates to a high-performance wear-resistant granite ceramic tile for public places and a preparation method thereof. Background Art

[0002] Granite is a common decorative material. It is composed of naturally formed stone rocks, mainly composed of minerals such as quartz, feldspar and mica. It is extremely hard and resistant to weathering and corrosion. It is the main building material for outdoor public places and is widely used. However, as a non-renewable resource, granite has begun to show a trend of resource depletion over time. In order to protect mineral resources, the country has strictly controlled the mining of granite. This measure has had a huge impact on the outdoor building materials market. As a result, people are eager to seek a building material that can replace granite.

[0003] At this time, granite tiles came into being. Granite tiles are both beautiful and exquisite, practical and efficient, and have obvious advantages: first, they are cost-effective. The price of granite ceramics is generally only one-half to one-third of that of stone; second, they have low radioactivity. The production of ceramic tiles has strict control standards for radioactivity. Compared with natural stone, there is no need to worry about radioactivity problems and they can be used in large quantities in indoor scenes; third, they have high flexural strength. Natural stone generally has some dark cracks that lead to insufficient strength. The strength of granite ceramics is 3-5 times that of natural stone, so they have higher durability; they have good pollution resistance. The surface of granite tiles is smooth and not easy to be stained with dirt. They are relatively easy to clean. They only need to be wiped with clean water and neutral detergent; fourth, the texture patterns are diverse and highly consistent. Granite tiles imitate the texture of natural granite. Through the selection of raw materials and production and deployment, more styles and patterns can be designed, and the consistency of the product production process can be guaranteed. At the same time, during use, phenomena such as quality changes and weathering of stone will not occur.

[0004] It can be seen that compared with stone, granite ceramic tiles have many advantages, but there are also two shortcomings that limit the large-scale replacement of stone by granite ceramic tiles. One is that the three-dimensional effect of the pattern decoration effect of ceramic tiles is weak, or the texture effect is not as rich as that of stone; the second is insufficient wear resistance. The hardness of the ceramic tile itself is still not as good as that of granite ceramics, or its pattern only exists in a thin layer of texture on the surface. The wear resistance is still far behind that of the stone with the same pattern inside and outside. Long-term use can easily cause the loss of pattern texture. For example, CN103553579B discloses an environmentally friendly full-body porcelain tile with natural granite characteristics and a preparation method thereof. The technical scheme is prepared through batching, ball milling, powder making, molding, glaze slurry preparation, glazing, printing, firing and natural cooling after leaving the kiln. Although this technology can produce granite with a surface texture close to that of natural granite, its disadvantage is that the surface texture is obtained by printing, the thickness of the pattern decoration layer is thin, and long-term use can easily cause the loss of pattern texture, and the surface wear resistance is poor. The poor three-dimensional decorative effect and insufficient wear resistance of granite ceramics greatly limit their wide application in public scenes, and most of them can only be used as ordinary ceramic products for indoor decoration. Therefore, the existing production technology of imitation granite ceramic tiles needs to be improved and developed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a method for preparing a green body by adopting a complex phase green body formula and combining three-dimensional fabric and particle preparation technology, so as to obtain a green body with high hardness, good wear resistance, good pollution resistance, high strength and low radioactivity, and can perfectly present the three-dimensional texture effect of granite stone, which can be widely used in the decoration of public places. High-performance wear-resistant granite ceramic tiles for public places and their preparation method can meet the needs of floor paving decoration in public places.

[0006] The technical solution of the present invention is the high-performance wear-resistant granite ceramic tile for public places, which is special in that it includes a multiphase wear-resistant ceramic body, and the multiphase wear-resistant ceramic body formula is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high-purity anatase titanium dioxide powder 0% to 5%, body reinforcing agent 0 to 1%, and debonding agent 1 to 3%;

[0007] The multiphase wear-resistant blank formula consists of the following chemical components by weight percentage: Al2O3: 30-40wt%, SiO2: 45-55wt%, K2O: 1-3wt%, Fe2O3: 0-2wt%, Na2O: 1-3wt%, CaO: 0-0.5wt%, MgO: 0.5-2.5wt%, and loss on ignition: 0-5wt%.

[0008] Preferably, the fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100wt%, a Fe2O3 content of 0-1wt%, and a particle size D50 < 3μm;

[0009] The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: particle size D50 is between 4μm and 8μm, Al2O3: 15-20wt%, SiO2: 65-75wt%, K2O: 2-5wt%, Fe2O3: 0-4wt%, Na2O: 2-5wt%, CaO: 0-2wt%, MgO: 0-1wt%, Li2O: 0.3-1wt%, trace elements: 0.1-1wt%, ignition loss 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, nickel

[0010] The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm;

[0011] The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.

[0012] Another technical solution of the present invention is a method for preparing the high-performance wear-resistant granite ceramic tile for public places, which is special in that it comprises the following steps:

[0013] ⑴ Preparation of composite wear-resistant ceramic body formula slurry: The raw materials in the body formula are mixed in proportion and ball-milled to obtain composite wear-resistant body formula slurry, which is then sent to the transfer slurry pool for storage and aging;

[0014] (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the composite wear-resistant body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use;

[0015] ⑶ Preparation of granular materials of different colors: granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;

[0016] (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are mixed evenly according to the designed ratio to obtain a mixed powder for standby use;

[0017] (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture;

[0018] (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank;

[0019] ⑺ Wear-resistant body drying: The formed wear-resistant body is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa;

[0020] (8) Kiln firing: sending the ceramic body of step (7) into a roller kiln for firing;

[0021] ⑼ Cold processing: The fired semi-finished products are polished or not polished and ground, and finally high-performance wear-resistant granite ceramic tiles with polished, natural or special-shaped surfaces are obtained.

[0022] As preferred: the composite wear-resistant ceramic body formula in the step (1) is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, body reinforcing agent 0 to 1%, and debonding agent 1 to 3%;

[0023] The multiphase wear-resistant blank formulation is composed of the following chemical components by weight percentage: Al2O3: 30-40wt%, SiO2: 45-55wt%, K2O: 1-3wt%, Fe2O3: 0-2wt%, Na2O: 1-3wt%, CaO: 0-0.5wt%, MgO: 0.5-2.5wt%, loss on ignition: 0-5wt%;

[0024] In the step (1), the processing of the composite wear-resistant green body formula adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm.

[0025] Preferably, the fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100wt%, a Fe2O3 content of 0-1wt%, and a particle size D50 < 3μm;

[0026] The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: particle size D50 is between 4μm and 8μm, Al2O3: 15-20wt%, SiO2: 65-75wt%, K2O: 2-5wt%, Fe2O3: 0-4wt%, Na2O: 2-5wt%, CaO: 0-2wt%, MgO: 0-1wt%, Li2O: 0.3-1wt%, trace elements: 0.1-1wt%, ignition loss 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, and nickel;

[0027] The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm;

[0028] The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.

[0029] Preferably, in step (2), the spray drying tower adopts a pressure spray drying system, uses a nozzle sheet combination with an aperture of 1.5 mm to 2.0 mm, an atomization pressure of 1.8 MPa to 2.6 MPa, a drying chamber diameter greater than 10 m, a drying output of 10 to 30 t / h, and the particle gradation of the obtained powder is: the proportion of particles on the 20-mesh sieve is less than 6%, the proportion of particles between 20 mesh and 40 mesh is 20%-25%, the proportion of particles between 40 mesh and 60 mesh is 40% to 45%, the proportion of particles between 60 mesh and 80 mesh is 15% to 20%, the proportion of particles below 80 mesh is less than 3%, and the specific gravity of the powder is 0.85 to 0.95 g / cm 3 , the moisture content is controlled at: 6-8%, and the angle of repose is controlled at 33°-38°;

[0030] The color powder in step (2) is composed of the following components by weight percentage: multiphase wear-resistant body formula slurry: 90-100wt%, ceramic colorant: 0-5wt%, emulsifier: 0-10wt%; the color powder is provided with 2-10 different types of colors;

[0031] The ceramic pigment in step (2) is composed of the following components: cobalt blue: 0-100wt%, manganese red: 0-100wt%, apple green: 0-100wt%, chrome green: 0-100wt%, orange: 0-100wt%, praseodymium yellow: 0-100wt%, cobalt black: 0-100wt%;

[0032] The opacifying agent is composed of the following components by weight percentage: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%.

[0033] As a preferred embodiment: the granulation equipment in step (3) comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and the discharging device is arranged above the conveyor belt, and the scraping device, the pressure roller and the cutter are arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder in step (2) on the surface of the conveyor belt in multiple layers according to the design parameters, and the scraping device is used to scrape the powder at a fixed height according to the particle thickness requirement, and then the pressure roller is used to press the powder into a block, and finally the powder is transported to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage;

[0034] Step (3) The color particle material is set to 1 to 5 kinds, the particle size is controlled to be 3 to 20 mm, the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥ 0.1 Mpa, and the density is controlled to be ≥ 1.0 g / cm 3 ;

[0035] In step (4), the mixed powder is provided with 2 to 6 kinds, and is composed of the following components by weight percentage: color powder: 0 to 100 wt%, color particle material: 0 to 100 wt%.

[0036] As a preferred embodiment: the whole body fabric forming system described in step (5) comprises a whole body fabric platform, a pressing and forming platform, and a conveying mechanism; the whole body fabric platform is provided with a plurality of fabric mechanisms, and the fabric mechanisms of the whole body fabric platform are composed of a fabric hopper mechanism, a transition belt, a transition hopper, a grille, a transfer feeding hopper, and a movable feeding hopper; the fabric mechanisms are designed with a plurality of groups, which are arranged at the top of the whole body fabric platform, and the fabric mechanisms form a blank layer after fabricating according to the designed texture pattern, and the finished blank layer is conveyed to the transition hopper by the transition belt and fixed by the grille, and then conveyed to the mold cavity in the pressing and forming platform arranged at the tail end of the whole body fabric platform through the conveying mechanism, and is scraped flat by the movable feeding hopper and then pressed to obtain a wear-resistant blank;

[0037] In step (5), the blank layer is formed by a whole-body fabric forming system to form a granite pattern texture that is consistent from bottom to top, and its thickness can be controlled to be 18 mm to 80 mm.

[0038] As a preferred embodiment: in step (6) of the pressing forming, the pressing pressure is greater than 40 MPa, and the thickness of the wear-resistant green body layer is controlled to be 9 mm to 40 mm;

[0039] The drying time in step (7) is 50 to 120 minutes; the residual moisture content of the green body after drying is ≤ 0.5%;

[0040] In step (8), the kiln used for firing is longer than 300m, with an inner width greater than 2m, a firing temperature of 1180-1250°C, a firing time of 60-120 minutes, a water absorption rate of the fired product of ≤0.5%, and a Ra value of the product out of the kiln of between 1.5 and 3μm;

[0041] The cold processing described in step ⑼ includes two situations. The first situation is to directly grind the edge of the product obtained in step ⑻ after sintering; the second situation is to first polish the product obtained in step ⑻ and then grind the edge.

[0042] Preferably, the polishing is the polishing of the wear-resistant surface; the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are matched as follows: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] ⑴ The present invention provides a high-performance wear-resistant granite ceramic tile for public places. By using a complex phase wear-resistant green body formula for high-temperature firing, the reaction generates a variety of high-hardness wear-resistant crystals including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, calcium feldspar, cordierite, etc. These high-hardness wear-resistant crystals are not only of many types, but also of high content, thereby improving the wear resistance of the product.

[0045] ⑵The formula of the present invention is a complex wear-resistant green body formula, which has the following advantages: ①The formula introduces a large amount of fine corundum powder. Through the finely processed corundum powder, on the one hand, the aluminum content of the formula can be increased, and at the same time, the reaction activity of the green body in the sintering process can be increased, thereby promoting the formation of wear-resistant crystals such as mullite, feldspar, and corundum; ②The formula finely grinds the lithium tailings. In addition to conventional elements such as silicon, aluminum, potassium, and sodium, the lithium tailings also contain special elements such as rubidium, gallium, strontium, cadmium, and nickel, and have a high SiO2 content. Fine grinding can promote the fluxing effect of trace elements, and at the same time improve the reaction activity of SiO2 and promote the growth of quartz crystal phase. The introduction of lithium and the formation of quartz crystals can improve the wear resistance of granite ceramic tiles; ③The formula introduces ultrafine zirconium silicate and titanium dioxide powder, which can promote the formation of zircon and rutile crystals. Zircon and rutile crystals are both high-hardness substances, which can better improve the wear resistance of the product.

[0046] ⑶ The present invention provides a whole-body fabric production process and technology. By combining particle preparation, powder mixing, whole-body fabric and other technical processes, the preparation of high-performance wear-resistant granite ceramic tiles is completed, which solves the problems of insufficient flexural strength and wear resistance of traditional ordinary granite ceramics and natural granite products, expands the richness of pattern design, and achieves the whole-body decorative effect with precise matching of product pattern texture from the inside to the outside. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a diagram showing the physical phase detection results of the multiphase ceramic tile of the present invention;

[0048] Figure 2 This is the result of physical phase detection of traditional common ceramic tiles;

[0049] Figure 3 This is a rendering of the high-performance wear-resistant granite ceramic used in public places by the present invention;

[0050] Figure 4 It is a schematic diagram of the whole body cloth forming system of the present invention.

[0051] Main component symbols:

[0052] Whole body fabric platform 1 Fabric mechanism 11 Transition belt 12 Transition hopper 13 Grille 14 Transfer hopper 15 Movable feeding hopper 16 Pressing molding platform 2 Conveying mechanism 3 DETAILED DESCRIPTION

[0053] The present invention will be further described in detail below in conjunction with embodiments:

[0054] Example 1

[0055] The method for preparing high-performance wear-resistant granite ceramic tiles for public places comprises the following steps:

[0056] ⑴ Preparation of composite wear-resistant ceramic body formula slurry: The raw materials in the body formula are mixed in proportion and ball-milled to obtain composite wear-resistant body formula slurry, which is then sent to the transfer slurry pool for storage and aging;

[0057] The composite wear-resistant body formula is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, body reinforcing agent 0.35%, debonding agent 1.1%;

[0058] The multiphase wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;

[0059] The processing of the composite wear-resistant green body formula adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;

[0060] The fine corundum powder formula consists of the following chemical components by weight percentage: Al2O399.94% α-Al2O3, Fe2O3 content of 0.06%, and particle size D50 of 1.86 μm.

[0061] The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O317.83wt%, SiO269.11wt%, K2O 3.50wt%, Fe2O30.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, and ignition loss 3.39wt%; the particle size D50 of the finely ground lithium tailings is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel; the ZrO2 content of the ultrafine zirconium silicate is 64.8%, and the particle size D50 is 0.82μm;

[0062] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2, a volatile matter at 105° of 0.3%, a 325-mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;

[0063] (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the composite wear-resistant body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use;

[0064] The color powder is set to eight kinds, and the specific settings are as follows:

[0065] The white powder is composed of the following components by weight percentage: multiphase wear-resistant green body formula slurry: 90wt%, emulsifier: 10wt%;

[0066] The apricot color powder is composed of the following components by weight percentage: composite wear-resistant green body formula slurry: 99.4wt%, manganese red material: 0.3wt%, orange material: 0.3wt%;

[0067] The gray powder is composed of the following components by weight percentage: multiphase wear-resistant blank formula slurry: 99.7wt%, cobalt black material: 0.2wt%, orange material: 0.1wt%;

[0068] The green color powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 99.4wt%, apple green material: 0.5wt%, chrome green material: 0.1wt%;

[0069] The black color powder is composed of the following components by weight percentage: composite wear-resistant blank formula slurry: 98.8wt%, cobalt black material: 1.1wt%, manganese red material: 0.1wt%;

[0070] The brown powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 97.3wt%, cobalt black material: 0.4wt%, praseodymium yellow material: 0.7wt%, manganese red material 1.6;

[0071] The yellow powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 98.4wt%, orange material: 0.6wt%, praseodymium yellow material: 1.0wt%;

[0072] The red color powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 98.4wt%, manganese red material: 1.3wt%, praseodymium yellow material: 0.3wt%;

[0073] The spray drying tower adopts a pressure spray drying system, uses a nozzle sheet with an aperture of 1.8 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter of 12.5 m, a drying output of 20 t / h, and obtains a particle gradation of the powder: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;

[0074] (3) Preparation of granular materials of different colors: granulating a portion of the color powder of step (2) through a granulating device to obtain granular materials of different colors;

[0075] The color particle materials are provided in four types, specifically white particles, black particles, brown particles, and yellow particles;

[0076] The granulation equipment comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and scraping devices, pressure rollers and cutters respectively arranged behind the discharging devices along the running direction of the conveyor belt; the discharging device spreads a total of four different color powders, namely, the white color powder, the black color powder, the brown color powder and the yellow color powder in step (2) on the surface of the conveyor belt in multiple layers according to design parameters, and the height is determined by the scraping device according to the particle thickness requirement, and after scraping, the pressure roller is pressed into a block, and finally transported to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage and standby; the granulation equipment can prepare particles with various effects, colors, thicknesses and specifications;

[0077] The color particles have a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a density of 1.61 g / cm 3 :

[0078] (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are mixed evenly according to the designed ratio to obtain a mixed powder for standby use;

[0079] The mixed powder is provided in four types according to the design requirements, including:

[0080] A mixed powder is composed of the following components by weight percentage: white particles: 10wt%, black particles: 5wt%, apricot color powder: 30wt%, gray color powder: 55wt%;

[0081] Mixed powder B is composed of the following components by weight percentage: brown particles: 8wt%, yellow particles: 15wt%, white particles: 5wt%, black color powder: 3wt%, gray color powder: 69wt%;

[0082] Mixed powder C is composed of the following components by weight percentage: brown particles: 5wt%, yellow particles: 20wt%, white particles: 10wt%, red color powder: 15wt%, gray color powder: 40wt%, green color powder: 10wt%;

[0083] The mixed powder D is composed of the following components by weight percentage: yellow powder: 15wt%, apricot powder: 35wt%, black powder: 3wt%, grey powder: 47wt%;

[0084] (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture;

[0085] The whole body fabric forming system described in step (5) comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform 1 is composed of a fabric mechanism 11, a transition belt 12, a transition hopper 13, a grille 14, a transfer feeding hopper 15, and a movable feeding hopper 16. The fabric mechanism 11 is designed with 6 groups, which are arranged at the top of the whole body fabric platform 1. The fabric mechanism 11 forms a blank layer after fabricating according to the designed texture pattern. The blank layer is conveyed to the transition hopper 13 by the transition belt 12 and fixed by the grille 14, and then conveyed to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole body fabric platform 1 through the conveying mechanism 3. The movable feeding hopper 16 feeds the material and scrapes it flat, and then presses and forms a wear-resistant blank;

[0086] The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm;

[0087] (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank;

[0088] The pressing pressure of the pressing molding is 45MPa, and the wear-resistant blank has a thickness of 20mm;

[0089] ⑺ Wear-resistant body drying: The formed wear-resistant body is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;

[0090] The drying time of the wear-resistant green body is 110 minutes; the residual moisture of the green body after drying is 0.42%;

[0091] (8) Kiln firing: sending the ceramic body of step (7) into a roller kiln for firing;

[0092] The kiln used for firing is 380m long, 2.2m wide, 1220°C in temperature, 75 minutes in time, the water absorption of the fired product is 0.06%, and the Ra value of the product out of the kiln is 1.72Ra;

[0093] ⑼Cold processing: Polish and grind the semi-finished products after firing to finally obtain polished high-performance wear-resistant granite ceramic tiles.

[0094] The polishing is decorative wear-resistant surface polishing; the polishing process parameters are: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive block combination: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and the Ra value of the product after polishing is 0.052μm.

[0095] Comparative Example 1

[0096] The invention discloses a high-performance wear-resistant granite ceramic tile for public places, wherein the green body formula is composed of the following components by weight percentage (traditional common green body formula): 20% of 35# stone powder, 28% of ultra-white washed mud, 25% of potassium sodium stone powder, 9.5% of water-abrasive, 3% of superplastic clay, 5% of talc particles, 8% of common mud paste, 0.45% of green body reinforcing agent and 1.05% of debonding agent.

[0097] The difference between Comparative Example 1 and Example 1 is that the multiphase wear-resistant green body formula of Example 1 is replaced with a traditional common green body formula. The preparation method of Comparative Example 1 is the same as that of Example 1.

[0098] Specifically, the methods of Example 1 and Comparative Example 1 were used to prepare granite ceramic tiles, and the obtained ceramic tiles and polished natural granite were tested for unglazed tile wear depth, flexural strength, water absorption, and Mohs hardness according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 1 below:

[0099] Table 1 Example 1, Comparative Example 1 and natural granite (polished surface)

[0100]

[0101] The test results of Example 1, Comparative Example 1 and polished natural granite show that when the multiphase wear-resistant body formula of the present invention is replaced with the common body formula, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic tile will be significantly reduced. Figure 1 and Figure 2 The results of phase detection show that the use of the complex wear-resistant green body formula generates more crystal phases than the traditional ordinary green body formula, including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite and other high-hardness wear-resistant crystals. Not only are there many types of crystal phases, but also the content is high. Therefore, the wear resistance of the granite ceramic prepared in Example 1 is significantly higher than that of Comparative Example 1 and natural granite.

[0102] Example 2

[0103] The method for preparing high-performance wear-resistant granite ceramic tiles for public places comprises the following steps:

[0104] ⑴ Preparation of composite wear-resistant ceramic body formula slurry: The raw materials in the body formula are mixed in proportion and ball-milled to obtain composite wear-resistant body formula slurry, which is then sent to the transfer slurry pool for storage and aging;

[0105] The composite wear-resistant body formula is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, body reinforcing agent 0.35%, debonding agent 1.1%;

[0106] The multiphase wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;

[0107] The processing of the composite wear-resistant green body formula adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;

[0108] The fine corundum powder formula consists of the following chemical components by weight percentage: Al2O399.94% α-Al2O3, Fe2O3 content of 0.06%, and particle size D50 of 1.86 μm.

[0109] The chemical composition of the finely ground lithium tailings consists of the following components by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, and ignition loss 3.39wt%; the particle size D50 of the finely ground lithium tailings is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel;

[0110] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;

[0111] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2, a volatile matter at 105° of 0.3%, a 325-mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;

[0112] (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the composite wear-resistant body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use;

[0113] The color powder is set to eight kinds, and the specific settings are as follows:

[0114] The white powder is composed of the following components by weight percentage: multiphase wear-resistant green body formula slurry: 90wt%, emulsifier: 10wt%;

[0115] The apricot color powder is composed of the following components by weight percentage: composite wear-resistant green body formula slurry: 99.4wt%, manganese red material: 0.3wt%, orange material: 0.3wt%;

[0116] The gray powder is composed of the following components by weight percentage: multiphase wear-resistant blank formula slurry: 99.7wt%, cobalt black material: 0.2wt%, orange material: 0.1wt%;

[0117] The green color powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 99.4wt%, apple green material: 0.5wt%, chrome green material: 0.1wt%;

[0118] The black color powder is composed of the following components by weight percentage: composite wear-resistant blank formula slurry: 98.8wt%, cobalt black material: 1.1wt%, manganese red material: 0.1wt%;

[0119] The brown powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 97.3wt%, cobalt black material: 0.4wt%, praseodymium yellow material: 0.7wt%, manganese red material 1.6;

[0120] The yellow powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 98.4wt%, orange material: 0.6wt%, praseodymium yellow material: 1.0wt%;

[0121] The red color powder is composed of the following components by weight percentage: composite wear-resistant body formula slurry: 98.4wt%, manganese red material: 1.3wt%, praseodymium yellow material: 0.3wt%;

[0122] The spray drying tower adopts a pressure spray drying system, uses a nozzle sheet with an aperture of 1.8 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter of 12.5 m, a drying output of 20 t / h, and obtains a particle gradation of the powder: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;

[0123] ⑶ Preparation of granular materials of different colors: granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;

[0124] The color particle materials are provided in four types, specifically white particles, black particles, brown particles, and yellow particles;

[0125] The granulation equipment comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and scraping devices, pressure rollers and cutters respectively arranged behind the discharging devices along the running direction of the conveyor belt; the discharging device spreads a total of four different color powders, namely, the white color powder, the black color powder, the brown color powder and the yellow color powder in step (2) on the surface of the conveyor belt in multiple layers according to design parameters, and the height is determined by the scraping device according to the particle thickness requirement, and after scraping, the pressure roller is pressed into a block, and finally transported to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage and standby; the granulation equipment can prepare particles with various effects, colors, thicknesses and specifications;

[0126] The color particles have a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a density of 1.61 g / cm 3 :

[0127] (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are mixed evenly according to the designed ratio to obtain a mixed powder for standby use;

[0128] The mixed powder is provided in four types according to the design requirements, including:

[0129] A mixed powder is composed of the following components by weight percentage: white particles: 10wt%, black particles: 5wt%, apricot color powder: 30wt%, gray color powder: 55wt%;

[0130] Mixed powder B is composed of the following components by weight percentage: brown particles: 8wt%, yellow particles: 15wt%, white particles: 5wt%, black color powder: 3wt%, gray color powder: 69wt%;

[0131] Mixed powder C is composed of the following components by weight percentage: brown particles: 5wt%, yellow particles: 20wt%, white particles: 10wt%, red color powder: 15wt%, gray color powder: 40wt%, green color powder: 10wt%;

[0132] The mixed powder D is composed of the following components by weight percentage: yellow powder: 15wt%, apricot powder: 35wt%, black powder: 3wt%, grey powder: 47wt%;

[0133] (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture;

[0134] See also Figure 4As shown, the whole body fabric forming system described in step (5) comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform is composed of a fabric mechanism 11, a transition belt 12, a transition hopper 13, a grille 14, a transfer feeding hopper 15, and a movable feeding hopper 16. The fabric mechanism 11 is designed with 6 groups, which are arranged at the top of the whole body fabric platform 1. The fabric mechanism 11 forms a blank layer after fabricating according to the designed texture pattern. The blank layer is conveyed to the transition hopper 13 by the transition belt 12 and fixed by the grille 14, and then conveyed to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole body fabric platform 1 through the conveying mechanism 3. The movable feeding hopper 16 feeds the material and scrapes it flat, and then presses and forms a wear-resistant blank;

[0135] The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm;

[0136] (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank;

[0137] The pressing pressure of the pressing molding is 45MPa, and the wear-resistant blank has a thickness of 20mm;

[0138] ⑺ Wear-resistant body drying: The formed wear-resistant body is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;

[0139] The drying time of the wear-resistant green body is 110 minutes; the residual moisture of the green body after drying is 0.42%;

[0140] (8) Kiln firing: sending the ceramic body of step (7) into a roller kiln for firing;

[0141] The kiln used for firing is 380m in length, 2.2m in inner width, 1220°C in temperature, 75 minutes in time, the water absorption of the product after firing is 0.06%, and the Ra value of the product out of the kiln is 1.72.

[0142] ⑼ Cold processing: Grind the edges of the fired semi-finished products to obtain high-performance wear-resistant granite ceramic tiles with a natural surface.

[0143] Comparative Example 2

[0144] The invention discloses a high-performance wear-resistant granite ceramic tile for public places, wherein the green body formula is composed of the following components by weight percentage (traditional common green body formula): 20% of 35# stone powder, 28% of ultra-white washed mud, 25% of potassium sodium stone powder, 9.5% of water-abrasive, 3% of superplastic clay, 5% of talc particles, 8% of common mud paste, 0.45% of green body reinforcing agent and 1.05% of debonding agent.

[0145] The difference between Comparative Example 2 and Example 2 is that the multiphase wear-resistant green body formula of Example 2 is replaced by a conventional common green body formula. The preparation method of Comparative Example 2 is the same as that of Example 2.

[0146] Specifically, the methods of Example 2 and Comparative Example 2 were used to prepare granite ceramic tiles, and the obtained ceramic tiles and natural granite with natural surface were tested for wear depth, flexural strength, water absorption, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 1 below:

[0147] Table 2 Example 2, Comparative Example 2 and natural granite (natural surface)

[0148]

[0149] The test results of Example 2, Comparative Example 2 and natural granite show that when the multiphase wear-resistant body formula of the present invention is replaced with the traditional common body formula, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic plate will be significantly reduced. Figure 1 and Figure 2 The results of phase detection show that the use of the complex wear-resistant green body formula generates more crystal phases than the ordinary green body formula, including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite and other high-hardness wear-resistant crystals. Not only are there many types of crystal phases, but also the content is high. Therefore, the wear resistance of the granite ceramic prepared according to Example 2 is significantly higher than that of Comparative Example 2 and natural granite.

[0150] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.

Claims

1. A high-performance wear-resistant granite ceramic tile for public places, characterized in that: The invention comprises a multiphase wear-resistant ceramic body, wherein the multiphase wear-resistant ceramic body is composed of the following raw material components by weight percentage: 8% to 15% ball clay, 8% to 15% high white kaolin, 10% to 15% mixed mud, 0% to 5% burnt talc, 3% to 6% bentonite, 15% to 25% potassium sodium stone powder, 8% to 15% finely ground lithium tailings, 4% to 8% calcined bauxite, 15% to 25% fine corundum powder, 0% to 5% ultrafine zirconium silicate, 0% to 5% high-purity anatase titanium dioxide powder, 0% to 1% body reinforcing agent, and 1% to 3% debonding agent; The multiphase wear-resistant blank formula consists of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 0-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%.

2. The high-performance wear-resistant granite ceramic tile for public places according to claim 1 is characterized in that: The fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100wt%, a Fe2O3 content of 0-1wt%, and a particle size D50 <3μm; The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements 0.1-1wt%, ignition loss 0-5wt%; the particle size D50 is between 4μm and 8μm, the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, and nickel; The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm; The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.

3. A method for preparing high-performance wear-resistant granite ceramic tiles for public places, characterized in that: The following steps are involved: ⑴ Preparation of composite wear-resistant ceramic body formula slurry: The raw materials in the body formula are mixed in proportion and ball-milled to obtain composite wear-resistant body formula slurry, which is then sent to the transfer slurry pool for storage and aging; (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the composite wear-resistant body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use; ⑶ Preparation of granular materials of different colors: granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors; (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are uniformly mixed according to the designed ratio to obtain a mixed powder for standby use; (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture; (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank; ⑺ Wear-resistant body drying: The formed wear-resistant body is sent to the roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa; (8) Kiln firing: sending the ceramic body of step (7) into a roller kiln for firing; ⑼ Cold processing: The fired semi-finished products are polished or not polished and ground, and finally high-performance wear-resistant granite ceramic tiles with polished, natural or special-shaped surfaces are obtained.

4. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 3, characterized in that: The composite wear-resistant ceramic body formula in step (1) is composed of the following raw material components by weight percentage: ball clay 8% to 15%, high white kaolin 8% to 15%, mixed mud 10% to 15%, burned talc 0% to 5%, bentonite 3 to 6%, potassium sodium stone powder 15 to 25%, finely ground lithium tailings 8% to 15%, calcined bauxite 4% to 8%, fine corundum powder 15% to 25%, ultrafine zirconium silicate 0% to 5%, high purity anatase titanium dioxide powder 0% to 5%, body reinforcing agent 0 to 1%, and debonding agent 1 to 3%; The multiphase wear-resistant blank formulation is composed of the following chemical components by weight percentage: Al2O3: 30-40wt%, SiO2: 45-55wt%, K2O: 1-3wt%, Fe2O3: 0-2wt%, Na2O: 1-3wt%, CaO: 0-0.5wt%, MgO: 0.5-2.5wt%, loss on ignition: 0-5wt%; In the step (1), the processing of the composite wear-resistant green body formula adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm.

5. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 4, characterized in that: The fine corundum powder is α-Al2O3 with an Al2O3 content of 99-100wt%, a Fe2O3 content of 0-1wt%, and a particle size D50 <3μm; The chemical composition of the finely ground lithium tailings is composed of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements 0.1-1wt%, ignition loss 0-5wt%; the particle size D50 is between 4μm and 8μm, the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, and nickel; The ultrafine zirconium silicate has a ZrO2 content of >64% and a particle size D50 of <1 μm; The high-purity anatase titanium dioxide powder is anatase titanium dioxide powder with a TiO2 content of more than 98%, a powder whiteness value of ≥96, volatile matter at 105°≦0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1 μm.

6. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 3, characterized in that: Step (2) The spray drying tower adopts a pressure spray drying system, uses a nozzle sheet combination with an aperture of 1.5 mm to 2.0 mm, an atomization pressure of 1.8 MPa to 2.6 MPa, a drying chamber diameter greater than 10 m, a drying output of 10 to 30 t / h, and the particle grading of the obtained powder is: the proportion of particles on the 20 mesh sieve is <6%, the proportion of particles between 20 mesh and 40 mesh is 20%-25%, the proportion of particles between 40 mesh and 60 mesh is 40% to 45%, the proportion of particles between 60 mesh and 80 mesh is 15% to 20%, the proportion of particles below 80 mesh is <3%, and the specific gravity of the powder is 0.85 to 0.95 g / cm 3 , the moisture content is controlled at: 6-8%, and the angle of repose is controlled at 33°-38°; The color powder in step (2) is composed of the following components by weight percentage: multiphase wear-resistant body formula slurry: 90-100wt%, ceramic colorant: 0-5wt%, emulsifier: 0-10wt%; the color powder is provided with 2-10 different types of colors; The ceramic pigment in step (2) is composed of the following components: 0-100wt% cobalt blue, 0-100wt% manganese red, 0-100wt% apple green, 0-100wt% chrome green, 0-100wt% orange yellow, 0-100wt% praseodymium yellow, and 0-100wt% cobalt black; The opacifying agent is composed of the following components by weight percentage: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%.

7. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 3, characterized in that: The granulation equipment in step (3) comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, wherein the discharging device is arranged above the conveyor belt, and the scraping device, the pressure roller and the cutter are arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder in step (2) on the surface of the conveyor belt in multiple layers according to the design parameters, and the scraping device is used to scrape the powder at a fixed height according to the particle thickness requirement, and then the pressure roller is used to press the powder into a block, and finally the powder is transported to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage; Step (3) The color particle material is set to 1 to 5 kinds, the particle size is controlled to be 3 to 20 mm, the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥ 0.1 Mpa, and the density is controlled to be ≥ 1.0 g / cm 3 ; In step (4), the mixed powder is provided with 2 to 6 kinds, and is composed of the following components by weight percentage: color powder: 0 to 100 wt%, color particle material: 0 to 100 wt%.

8. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 3, characterized in that: The whole body fabric forming system described in step (5) comprises a whole body fabric platform, a pressing and forming platform and a conveying mechanism; the whole body fabric platform is provided with a plurality of fabric mechanisms, and the fabric mechanisms of the whole body fabric platform are composed of a fabric hopper mechanism, a transition belt, a transition hopper, a grille, a transfer feeding hopper and a movable feeding hopper; the fabric mechanisms are designed with a plurality of groups, which are arranged at the top of the whole body fabric platform, and the fabric mechanisms form a blank layer after fabricating according to the designed texture pattern, and the finished blank layer is conveyed to the transition hopper by the transition belt and fixed by the grille, and then conveyed to the mold cavity in the pressing and forming platform arranged at the tail end of the whole body fabric platform through the conveying mechanism, and is scraped flat by the movable feeding hopper and then pressed and formed to obtain a wear-resistant blank; In step (5), the blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 18 mm to 80 mm.

9. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 3, characterized in that: In step (6), the pressing pressure is greater than 40 MPa, and the thickness of the wear-resistant green body layer is controlled to be 9 mm to 40 mm; The drying time in step (7) is 50 to 120 minutes; the residual moisture content of the green body after drying is ≤ 0.5%; In step (8), the kiln used for firing is longer than 300m, with an inner width greater than 2m, a firing temperature of 1180-1250°C, a firing time of 60-120 minutes, a water absorption rate of the fired product of ≤0.5%, and a Ra value of the product out of the kiln of between 1.5 and 3μm; The cold processing described in step ⑼ includes two situations. The first situation is to directly grind the edge of the product obtained in step ⑻ after sintering; the second situation is to first polish the product obtained in step ⑻ and then grind the edge.

10. The method for preparing high-performance wear-resistant granite ceramic tiles for public places according to claim 9, characterized in that: The polishing is the polishing of the wear-resistant surface; the polishing process parameters are: the polishing machine pressure is below 0.6Mpa, the polishing speed is 15-30m / min, the polishing abrasive blocks are matched as follows: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, the polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.

Citation Information

Patent Citations

  • Environment-friendly full body porcelain brick having characteristic of natural granite, and preparation method thereof

    CN103553579B

  • Foamed ceramic composite plate taking gold tailings and granite tailings as main materials and preparation method thereof

    CN109502981A

  • Distribution device, distribution method and preparation method for whole body granite ceramic tiles

    CN111037729A

  • Thin ceramic rock plate and preparation method thereof

    CN111470856A

  • Beneficiation method for trace tantalum, niobium and lithium in rubidium-containing granite

    CN117206067A